Faktor Resiko Penyebab Perdarahan Postpartum - Ariyani Lutfitasari; Lia Mulyanti; Sherkia Ichtiarsi Prakasiwi; Indri Astuti Purwanti; Thoyyibatul Islami (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
One of the causes of the high maternal mortality rate in Indonesia is postpartum hemorrhage. Postpartum hemorrhage is an abnormal condition where the blood that comes out is very much up to 500 cc or even more. This case of postpartum hemorrhage can occur in all circles of pregnant women. AKI is one of the biggest problems in the health sector in developing countries and is mostly caused by bleeding. This study aims to determine what are the risk factors for postpartum hemorrhage. The type of research used in this study is a literature review research using 5 journals obtained from Google Scholar, this study uses two variables, the dependent variable and the independent variable. The dependent variable is postpartum hemorrhage and the independent variables are age, parity, delivery distance, hemoglobin level, duration of labor and previous delivery history. The most dominant factor in the incidence of postpartum hemorrhage is parity. It is hoped that further researchers will seek more references from various reliable sources to enrich the data